Mate choice and pair fidelity in a translocated population of North Island brown kiwi : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Zoology at Massey University, Manawatū, New Zealand - Ramos Pallares, Eliana (Massey University, 2025)
Aotearoa New Zealand is renowned for its high levels of endemism, yet it has also suffered profound species declines and extinctions following human settlement and the arrival of invasive species. Many species that once dominated New Zealand’s landscape are now confined to small, isolated populations with limited gene flow. Conservation translocations (the intentional movement and release of an organism inside its indigenous range from which it has disappeared) of kiwi (Apteryx spp.) are among the most common and increasingly important practices in New Zealand kiwi recovery programs. The success of translocations depends on animals securing food and shelter, avoiding predators, and, critically, finding mates to reproduce. Consequently, post‑release mate choice, pair fidelity, and divorce are key considerations, yet the roles of behavioural, genetic, and morphological traits in shaping these processes in translocated kiwi populations remain unclear. My thesis addresses this gap using a dense, translocated population of North Island (NI) brown kiwi (Apteryx mantelli) on Ponui Island as a study system. For this, I combine long-term behavioural monitoring, morphometric analyses, next-generation sequencing of MHC genes and Bayesian statistical modelling. My major findings indicate that: (1) fidelity probability increased with male incubation effort, such that the more days a male incubated, the greater the likelihood of the pair remaining together; (2) shared incubators in polygamous groups tend to invest less in nest attendance than single incubators, suggesting benefits linked to nest relief; (3) NI brown kiwi exhibits the highest allelic diversity and sequence polymorphism at MHC class IIβ yet reported for any ratite (4) The high MHC class IIβ in kiwi on Ponui Island likely reflect its mixed ancestry; (5) MHC IIβ exon 2 features did not appear to influence the formation of social pairings, yet males with higher MHC diversity showed a weak trend toward greater pair retention; (6) Morphological traits showed no evidence of assortative mating, and weak size-based correlations were largely explained by residual covariance rather than true mate choice. Collectively, this body of research offers valuable insights into how behavioural, genetic, and morphological factors interact to shape reproductive strategies in reintroduced populations, providing an empirical foundation for managing genetic health and pair dynamics in conservation translocations.
Keywords: Aotearoa New Zealand; Apteryx mantelli; breeding system; conservation translocation; divorce; inbreeding depression; incubation effort; kiwi; major histocompatibility complex; mate choice; mating strategy; monogamy; outbreeding depression; pair bond status; pair familiarity; phenotypic features; polygamy; Ponui Island; 310901 Animal behaviour; 310301 Behavioural ecology